Sustainable cities for water: the public policies for rectification and sanitation of the Providência channel, in Belém (Pará- Brazil) (Research, Society and Development, 2022)
The article discusses sustainable cities for water with a focus on public policies for rectification and sanitation of the Providência channel in the Maracangalha neighborhood of Belém. The study was conducted through a review of the literature on sustainable cities for water, basic sanitation, public policies, the rectification of river courses, fieldwork, and analysis through the production of a letter image of the neighborhood, presenting the process of occupation of the surrounding channel to trace qualitative and quantitative information of the environmental. The results showed that anthropic interventions have generated continuous problems for this environment, interfering in the dynamics of the channel, due to changes in the morphology of the area, due to the rectification process, as well as the waterproofing of the roads and the removal of much of the vegetation cover, accumulation of solid waste, silting and erosion of the channel, in addition to the dumping of sanitary sewage, corroborating for poor urban and environmental quality. In this sense, it is concluded that it is necessary to manage the waters in the urban space, with the valorization of vital water resources, encouraging public policies that rebalance and make sustainable the relationship of the population with the watercourses in the Providence channel.